THE INFLUENCE OF USING PICTURE SERIES AND REALIA TOWARD WRITING ABILITY - Fenny Thresia (Universitas Ahmad Dahlan)
Writing is a process of communication which uses a conventional graphic system to the reader. In writing subject especially descriptive text the students’ find some problem, such as: they find difficulties in developing their idea, their vocabulary is still low, they get difficulties to make sentences and the teacher uses unsuitable media as a tool to teach writing. The media presented as a solution are picture series and realia media. The objective of this research is to know whether there is more effective of using Picture Series and Realia Media. In this research the researcher uses quantitative research with quasi experimental design. The population in this researcher was 711 students at the tenth grade of SMA Negeri 1 Rumbia. It was consists of 20 classes and average each class consist of 36. The researcher used cluster sampling as technique sampling, the sample of this research is X3 as an experimental class and X4 as control class. To analyze the data, the researcher used ttest formula. The researcher got the result of ttest is 4,59 and ttable is 2,65 (on criterion 1) and 2,00 (So, on criterion 2). It means that thit>ttable. The criterion of ttest is Ha accepted if thit>ttable. There is different result of students writing ability in descriptive text using picture series and realia media. Picture series is more effective than realia media toward students’ writing ability in descriptive text, the statement is proven by result of posttest and hypothesis test.